Dynamics of liquid solidification : thermal resistance of contact layer - Lipnicki, Zygmunt (Springer, 2017)
This monograph comprehensively describes phenomena of heat flow during phase change as well as the dynamics of liquid solidification, i.e. the development of a solidified layer. The book provides the reader with basic knowledge for practical designs, as well as with equations which describe processes of energy transformation. The target audience primarily comprises researchers and experts in the field of heat flow, but the book may also be beneficial for both practicing engineers and graduate students.
Keywords: Liquids -- Thermal properties.; elektronické knihy; electronic books